P618 Post-operative Crohn's disease patients undergoing colonoscopy require significantly more analgesia and sedation compared with a non-IBD population. (15th January 2020) - Rowan, C; Janjua, M; Foley, C; Burke, J; Boland, K; O'Toole, A
Abstract: Background: Rates of surgical intervention in Crohn's disease have declined. However, a significant proportion of patients still require surgical resection and have been shown to have higher post-op pain scores and analgesia requirements. The aim of this study was to assess sedation requirements and comfort scores of post-operative Crohn's disease patients at endoscopy. Methods: Patients with a previous intestinal resection undergoing colonoscopy in 2017 were identified using an electronic reporting system. Data regarding patient demographics, disease characteristics, sedation requirements, comfort scores and endoscopy reports were collected. Patients with Crohn's disease were compared with a non-IBD post-op population. Results: n = 153 patients were included. n = 56 Crohn's disease, n = 2 UC and n = 95 non-IBD patients underwent colonoscopy. Patient characteristics in Table 1. 13.6% of patients had a documented history of chronic pain or other relevant conditions that may affect comfort scores. 68.3% of patients with Crohn's disease were on therapy at the time of endoscopy. The median dose of midazolam administered was 3 mg (IQR 2–4 mg); median fentanyl dose was 50 μg. (IQR 50–75 μg). The median dose of Midazolam was significantly higher in patients with Crohn's disease (3 mg IQR 3–4 mg vs. 3 mg IQR 2–3; p = 0.006). The median dose of fentanyl required was also significantly higher in post-operative Crohn's patients (50 μg IQR 50–100 μg vs. 50 μg; p = 0.001). The median comfort score in Crohn's disease patients was higher (indicating more discomfort) when compared with the non-IBD cohort. (median score 2 and 1 respectively) There was no significant difference in the proportion of patients with chronic pain or multiple intestinal resections ( p = 0.84 and p = 0.142). There was a statistically significant difference in comfort scores; n = 19 Crohn's disease patients (39.6%) had comfort score 1, compared with n = 70 non-IBD patients (71.4%) ( p = 0.04). There was no significant difference in the median doses of midazolam or fentanyl when comparing Crohn's disease patients with and without active endoscopic disease. ( p = 0.07 and p = 0.10 respectively). Conclusion: Patients with Crohn's disease undergoing colonoscopy in the post-operative setting have significantly higher analgesia requirements. Comfort scores are significantly worse when compared with non-IBD patients who have had similar intestinal resections. Endoscopists should use techniques, e.g. CO2 insufflation in addition to medication to ensure comfort amongst patients with Crohn's disease.